Insolvency Resolution and the Missing High-Yield Bond Markets - Becker, Bo; Josephson, Jens (Review of Financial Studies, 2016)
In many countries, poorly functioning bankruptcy procedures force viable but insolvent firms to restructure out of court, where banks may have a bargaining advantage over other creditors. We model the choice of restructuring process and derive implications for the corporate mix of bank and bond financing. Empirical patterns match the model: inefficient bankruptcy in a country is associated with less bond issuance by risky, but not by safe, borrowers. This pattern holds for both levels of and changes in bankruptcy recovery. Our results establish a link between bankruptcy reform and corporate bond markets, especially high-yield markets.